The Effect of Video-Based Education on Knowledge of Bonding Attachment among Working Postpartum Mothers in the Working Area of TPMB Marsini Karni, Pontianak City - Nur'aini Nur'aini; Oon Fatonah Akbarini; Rini Sulistiawati; Rakhmawati Rakhmawati; Emy Yulianti (Media Ilmiah Kesehatan Indonesia, 2026)
The postpartum period is a critical phase for both mothers and infants, as it marks the early formation of emotional closeness through bonding attachment. Among working postpartum mothers, this process may face challenges due to limited time, fatigue, and work-related demands. Video-based education is a potential strategy to improve maternal knowledge because it is engaging, easy to understand, and can be reviewed independently. This study aimed to analyze the effect of video-based education on improving knowledge of bonding attachment among working postpartum mothers in the working area of TPMB Marsini Karni, Pontianak City. This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 22 respondents were selected using consecutive sampling. Data were collected using a knowledge questionnaire on bonding attachment. Data were analyzed using the Wilcoxon Signed-Rank Test because the data were not normally distributed. The results showed that the median knowledge score increased from 13, with a range of 10–14, in the pretest to 15, with a range of 15–16, in the posttest. The Wilcoxon Signed-Rank Test showed Z = -4.136 and p = 0.000 (p < 0.05). These findings indicate that video-based education had a significant effect on increasing knowledge of bonding attachment among working postpartum mothers. Video-based education can be used as a practical and flexible midwifery education strategy suitable for working postpartum mothers.